Quality of Life in Adolescent Idiopathic Scoliosis after Surgery: an Observational Study - Leonor Figo Araújo Coelho da Rocha (2022)
Purpose: This study aims to evaluate the post-surgery quality of life of patients with Adolescent Idiopathic Scoliosis (AIS), when compared to healthy control individuals, and to assess the relationship between their radiological outcomes and self-reported quality of life. Methods: In this cross-sectional study, surgically-treated AIS patients between 2014 and 2019 were enrolled, along with age matching controls. Quality of life (QoL) data was gathered using SF36 and SRS24 questionnaires in both groups. Pre and postoperative Cobb angles were measured to assess AIS patients' radiological evolution. Results: Forty-three AIS patients and fifty age-matched controls were enrolled. Except for SF36 general health and health change and SRS24 general self-image and functioning from back condition, all other QoL parameters were significantly higher in the control group. Apart from SRS24 postoperative self-image, no other parameter had a significant correlation with Cobb angle reduction. Conclusion: AIS patients, even about 5 years after surgery, reported an overall worst QoL, when compared to matched healthy individuals, but this reported QoL correlated poorly with correction of Cobb angle. This highlights the need for appropriate tools to assess the success of this procedure, rather than to rely solely on the radiological outcomes.